Chemistry of (and on) transition metal clusters: a Fourier transform ion cyclotron resonance study of the reaction of niobium cluster cations with nitric oxide. - Harding, D; Oliver, T; Walsh, T; Drewello, T; Woodruff, D; Derrick, P; Mackenzie, S (2009)
The reactions of niobium cluster cations, Nb(+)(n) (n = 2-19), with nitric oxide have been investigated using Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR). The overall reaction rate constants are found to be in reasonable agreement with collision rates calculated using the surface charge capture model. The dominant reaction for small clusters (n <9) involves reaction-induced fragmentation resulting in the loss of either NbO or NbN. By contrast, the main reaction observed for the larger clusters (n> 11) is sequential NO chemisorption. Clusters n = 9, 10 exhibit both extremes of behaviour and are the only clusters upon which there is evidence of NO decomposition with N(2) loss observed whenever multiple NO molecules are co-adsorbed. The rate constants for each process have been determined as a function of cluster size.